An Experimental Study on Virtual Machine Live Migration Impact on Services Performance - Bezerra, Petrônio; Santos, Marcela; Alves, Edlane; Albuquerque, Fellype; Martins, Gustavo; Gomes, Reinaldo; Costa, Anderson (Computing and Informatics, 2019)
One important benefit of servers' virtualization is the reduction of the maintenance complexity of infrastructures. A key feature is servers' live migration which allows virtual servers to be exchanged between physical machines without stopping their services. However, virtualization also has some drawbacks caused by the overhead generated. Our research evaluated live migration process overhead, on real and virtual environments, noticed from the client's side regarding two different services: web and database. YCSB and ab Benchmark were adopted as workloads. Almost all tests on real environment overcame those on virtual, with both benchmarks. The impact of the live migration in the services was evident, proving to be more effective on real machines than on virtual machines. We found the DB service accommodated better to the virtual environment and to migration than Web service. We also considered an environment with multiple migrations which presented a higher degradation than when only one migration is performed.